A sociological study on Chronic Kidney Disease (CKD) patients in the North Central province, Sri Lanka (with special reference to the Padawiya area) - Subasinghe, Wasantha (Culture, Globalization and the Developing World, 2nd ICSS, 2013)
Chronic kidney disease is a worldwide public health problem. It is also known as chronic renal disease or chronic renal failure, which is a degenerative, progressive condition marked by the gradual loss of kidney function. The experience is traumatic not only for the patients but also for their families who are frequently unable to provide the medical services needed due to the high cost of treatment. Optimally, CKD is treated with dialysis or kidney transplant. A chronic kidney disease of unknown etiology has emerged as a major health care problem in the North - Central Province of Sri Lanka during the last few decades. The aim of this study is to determine the prevalence of kidney disease and to identify the responsibility of the government and other authorities regarding solving this burning issue. The research problem is the Socio - economic impact of CKD in North central province. A survey was conducted to identify the research problem and data was collected using questionnaires, key informant interviews and focus group interviews. The research area was Padawiya in the Padawiya Divisional Secretariat. In developed countries, the most common symptoms of CKD are obesity, high blood pressure, and diabetes. But in Sri Lankan context there is a significantly high rate of kidney patients in the North Central province. A number of research has been conducted to identify the causes and effects of the disease. Different researchers have identified different causes including insecticides, fluoride water, poisons, arsenic, dehydration, drugs, smoking, hard metals etc. Research findings including spreading rate, sex ratio, geographical and environmental relations, food patterns, livelihood patterns, water resources have created new avenues for scholarly discussion on these issues.